1996
DOI: 10.1246/bcsj.69.349
|View full text |Cite
|
Sign up to set email alerts
|

Intercalation of Water in a Layered Perovskite Compound, NaEuTiO4

Abstract: Intercalation of water was observed in a layered perovskite compound, NaEuTiO4, leading to its hydrated derivatives. There are some metastable intermediates in the hydrated derivatives. The hydration process includes several steps that are topotactic. The crystal structure of the hydrated derivatives was identified by Rietveld analysis for the powder X-ray diffraction pattern. It is confirmed that the water molecules are inserted into the sodium layer of NaEuTiO4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 13 publications
3
17
0
Order By: Relevance
“…While the parent K¸nTiO phases are orthorhombic, preliminary evidence suggests that the hydrated phases are tetragonal, which is reasonable considering the signi"cant dependence of the interlayer structure of layered perovskites on the coordination and bonding of the intercalated water (27). Identical hydration behavior occurs for NaEuTiO , where the stable NaEuTiO ) 0.8H O hydrated phase appears tetragonal while the anhydrous NaEuTiO phase is orthorhombic (28 The hydrated K¸nTiO ) xH O (¸n"Nd, Sm, Eu, Gd, Dy) phases adopt an eclipsed rather than a staggered geometry. The shift of the perovskite slabs along the (110) direction (where the c axis is the stacking axis) is shown in the inset in Fig.…”
Section: Klntiomentioning
confidence: 56%
“…While the parent K¸nTiO phases are orthorhombic, preliminary evidence suggests that the hydrated phases are tetragonal, which is reasonable considering the signi"cant dependence of the interlayer structure of layered perovskites on the coordination and bonding of the intercalated water (27). Identical hydration behavior occurs for NaEuTiO , where the stable NaEuTiO ) 0.8H O hydrated phase appears tetragonal while the anhydrous NaEuTiO phase is orthorhombic (28 The hydrated K¸nTiO ) xH O (¸n"Nd, Sm, Eu, Gd, Dy) phases adopt an eclipsed rather than a staggered geometry. The shift of the perovskite slabs along the (110) direction (where the c axis is the stacking axis) is shown in the inset in Fig.…”
Section: Klntiomentioning
confidence: 56%
“…2b) consists of Ca Ta -TiO\ slabs that are eclipsed along the (110) direction. The eclipsed con"guration has been noted in other hydrated layered perovskites (20,28), and most likely allows better coordination of the interlayer potassium with the intercalated water.…”
Section: LImentioning
confidence: 69%
“…According to the previous report, the hydrous NaLa 2 Ti 2 TaO 10 $2H 2 O is transformed into an other hydrous phase, NaLa 2 Ti 2 TaO 10 $0.9H 2 O, by partial dehydration around 100 8C, and the symmetry of the hydrated structure is restored from I4/mmm to P4/mmm. Toda et al [13] have revealed that the amount of H 2 O molecule inserted in between the perovskite blocks is an important factor for hydrated phases derived from a layered perovskite NaEuTiO 4 which belongs to the nZ1 Ruddlesden-Popper compound. The crystal structure of the hydrous NaEuTiO 4 $xH 2 O with xZ0.5 had the space group I4/mmm, while hydrous phase with xZ0.8 was indexed as the space group P4/nmm.…”
Section: Resultsmentioning
confidence: 99%